Key factors affecting enterprise competitiveness and business efficiency: a case study of tourism enterprises in Vietnam - Phan Thanh Tam (Cogent Business & Management, 2024)
Vietnam's tourism business has been dramatically affected by the Covid‑19 outbreak, leading to a considerable decrease in the number of tourists visiting the country. Tourism is vital in creating national income, attracting investment, encouraging exports, and stimulating growth in linked economic sectors. Therefore, this study examines the primary determinants that affect the competitiveness of tourist firms and their influence on business efficiency. The study utilizes qualitative and quantitative approaches, drawing on data collected from a sample of 870 corporate managers in five big cities in Vietnam. Quantitative analysis includes descriptive statistics and structural equation model performed using SPSS 20.0 and Amos. The key findings identified six crucial factors that determine the competitiveness and efficiency of tourism enterprises: (1) Quality of products and services, (2) Marketing capacity 4.0, (3) Organizational and management capacity, (4) Brand promotion, (5) Human resource quality, and (6) Social responsibility. These factors significantly impact the enterprises' competitiveness and efficiency, with a significance level 0.01. These findings emphasize the significance of strategic policy actions to enhance these elements to promote post‑pandemic recovery and long‑term competitiveness in Vietnam's tourism sector. The result provides valuable insights to policymakers and tourist stakeholders, facilitating evidence‑based policy development to improve competitiveness and business efficiency in Vietnam's tourism industry after the Covid‑19 pandemic.
Keywords: 650; Competitiveness; tourism enterprises; business efficiency; policy implications